2002
DOI: 10.1002/pola.10210
|View full text |Cite
|
Sign up to set email alerts
|

Production of crosslinked, hollow nanoparticles by surface‐initiated living free‐radical polymerization

Abstract: Surface‐initiated living free‐radical polymerization is employed in a multistep procedure to prepare hollow polymeric nanocapsules. Initially, trichlorosilyl‐substituted alkoxyamine initiating groups are attached to the surface silanol groups of silica nanoparticles. This surface layer of initiating groups is then used to grow functionalized linear chains leading to a core–shell morphology. The choice of functional groups is governed by their ability to undergo facile crosslinking reactions, with both active e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
179
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(182 citation statements)
references
References 81 publications
3
179
0
Order By: Relevance
“…Surface-Initiated ARGET ATRP of MMA on SiO 2 Nanoparticle Surface-initiated ARGET ATRP of MMA on SiO 2 nanoparticles mediated by copper (Scheme 1) was carried out in the presence of the free initiator to control not only the graft polymerization but also to easily measure the molecular weight (and its distribution) of the resulting grafted PMMA [18,19,[32][33][34][35]. Table 1 shows the experimental conditions and properties of PMMA by surface-initiated ARGET ATRP at 608C.…”
Section: Resultsmentioning
confidence: 99%
“…Surface-Initiated ARGET ATRP of MMA on SiO 2 Nanoparticle Surface-initiated ARGET ATRP of MMA on SiO 2 nanoparticles mediated by copper (Scheme 1) was carried out in the presence of the free initiator to control not only the graft polymerization but also to easily measure the molecular weight (and its distribution) of the resulting grafted PMMA [18,19,[32][33][34][35]. Table 1 shows the experimental conditions and properties of PMMA by surface-initiated ARGET ATRP at 608C.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it was demonstrated that the thickness of the polymer layer increased linearly with the conversion. Blomberg et al [194] have also used this strategy on silica particles, using the copolymerization of styrene with a monomer that can be thermally cross-linked, thus giving core-shell particles. Using hydrofluoric acid to remove the silica core, authors obtained hollow cross-linked polymer spheres.…”
Section: Nmrpmentioning
confidence: 99%
“…Organic-inorganic nanocomposites have hybrid properties derived from synergistic reactions of the two components. The most promising composite systems are nanocomposites based on organic polymers and inorganic clay minerals [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%